Stress analysis in upper fillet and rail-end bolt hole at rail joint - SaiKham Le; Jittraporn Wongsa‐Ngam (IOP Conference Series Materials Science and Engineering, 2021)
Abstract Rail joint between two adjacent rail ends in the transportation of railway track structure is one of the weakest components leading to defects and failures. In this study, the rail joint components such as rail, joint bars, bolts, and sleeper are modelled by 3D Abaqus/CAE software and Finite-element method are used to investigate stress distribution in rail under static wheel load condition. The wheel load positions and bolt-hole locations vary as a parametric study. The results show that the critical stress occurs at the upper fillet rail end and at the edge of the rail-end bolt hole (1 st hole from the rail end). The wheel load position affects stress only in case of the rail-end bolt hole located at 80 mm from the end. In addition, overall trends for the effect of rail-end bolt hole positions are similar in which the stress decreases when the distance from rail end to the rail-end bolt hole increases. Taken together, these findings suggest stress distribution is the basic information that helps understand the failure mechanism.
Keywords: Railway Engineering and Dynamics; Engineering Structural Analysis Methods; Mechanical stress and fatigue analysis